THE SOCIAL CONTEXT OF THE DIALECTICAL STRUCTURE IN THE MACEDONIAN ART-MODERNIST DISCOURSE (Годишен зборник на Филозофски факултет - Скопје, 2025)
Through a summarized insight into the historical developmental stages in artand culture, this paper anticipates the hypothesis of the existence of a dialectical structurein the Macedonian art-modernist discourse, generated by the positions of the artist/art in relation to the complex social reality in Macedonia.Since the pre-war period, the subject of analysis has been art as a social practiceand the artist as a social actor (the founders of modern art, Ličenoski, Martinoski) who,through the theme of labor and the worker, provides an engaged response addressing thequestion of class consciousness. From the post-war period (the division of the world intoblocs, the clash of East and West) as a turning point, the paper explores the potential ofpublic speech (by Miroslav Krleža) as a call for freedom of artistic creation and as resistanceto imposed dogmas (socialist realism). The step towards a decisive dialectization ofart and culture is examined through the activities of the group “Denes” (a promisingstep), the democratization of art, and the “aesthetic pluralism” of its creators (Lazeski,Grabuloski). Post-war monumental art is analyzed through the aspect of man-society,that is, through the role of individual artistic impulses (Mazev, Čemerski) in the constructionof a new social system.In a continuity of crisis historical situations, the foundation of art is guided bythe need for participation in the construction of a new society, based on and constitutedby the dialectical attitudes and individual decisions of modernist artists.